Effectiveness and safety of intra-articular hyaluronic acid SEMICAL GEL-B CROSS therapy in knee osteoarthritis (SEM-ART1): Study protocol for a randomized, placebo controlled, double-blind, cross-over clinical trial - Meral Bilgilisoy Filiz; Hanife Hale Hekim; Ahmet Bal; Aslıhan Kara (PLoS ONE, 2026)
Objective This study aims to evaluate the effectiveness and safety of a single intra-articular injection of high-dose cross-linked hyaluronic acid on pain, physical function, muscle strength, and quality of life in patients with knee osteoarthritis. Methods This randomized, double-blind, placebo-controlled, cross-over clinical trial includes 102 adults with symptomatic knee osteoarthritis (Kellgren–Lawrence grade II–III). Participants will be allocated using stratified randomization based on radiographic severity and laterality. Patients will receive either intra-articular hyaluronic acid (Semical Gel-B Cross, 90 mg/3 mL) or isotonic saline (3 mL of 0.9% NaCl), followed by cross-over at the 3-month evaluation. Outcomes will be assessed at baseline and at 3, 6, 9, and 12 months. The primary efficacy endpoint is the between-group difference in WOMAC pain score at the 3-month assessment prior to cross-over. Secondary outcomes include VAS pain, WOMAC physical function and stiffness scores, isometric quadriceps and hamstring strength, quality of life (SF-36), the 6-minute walk test, the 5-times sit-to-stand test, analgesic use, and adverse events. Treatment response will additionally be categorized as “absolute responders” (≥50% and ≥20-point improvement in VAS) and “responders” (≥20% and ≥10-point improvement). Sample size was calculated using G*Power (effect size 0.5, 80% power), yielding 102 participants. Statistical analyses will include both intention-to-treat and per-protocol approaches. Expected results and conclusions This study will provide 3-month efficacy data and long-term (3–12 months) safety outcomes for high-dose intra-articular hyaluronic acid compared with placebo. Findings are expected to inform clinical decision-making regarding symptom relief, functional improvement, and the safety profile of cross-linked HA formulations in knee osteoarthritis. Trial registration ClinicalTrials.gov: NCT06141018